COSTUME DESIGN AND SOCIAL STATUS VISUALIZATION IN JAVANESE DANCE AT PURA MANGKUNEGARAN - Sriyadi, Sriyadi -; Pramutomo, R.M.; Sari, Yoni Wulan; Elvina, Luh (Paradigma: Jurnal Kajian Budaya, 2024)
The design of costumes holds a crucial role in visualizing the social status of characters in Javanese dance. By employing symbolic systems, costume design conveys this status to the audience. This study investigates the relationship between costume design and the depiction of social status in Javanese dance at Pura Mangkunegaran. Utilizing a qualitative methodology with an ethnocoreological approach, the research draws on a literature review as its primary data source. This review involves analyzing various documents, photographs, and videos. The findings indicate that accessories and attributes within costume design are integral to the symbolic system that represents social status. As an ethnic dance, the costume design in Mangkunegaran dance embodies the ethical and ethno-aesthetic values of the community, reflecting the life, worldview, and cultural expressions of the Javanese people. These values may evolve over time as the community’s perspectives shift.